Home away from home: landscape as a mediator between place and belonging in the peripheral areas of the Marche region in Italy. (2018) - Pezzi, Maria Giulia
This article looks at the possible intersections between emigration, immigration, multiple dwelling practices, tourism, and sense of place in the peripheral rural/mountain areas of the Marche region, Italy. It will do so by focusing on two different realities: 1) that of people who, in the last two decades, have emigrated from their small villages to pursue better career possibilities both in Italy and abroad; 2) that of foreign residents (mostly, but not only, definable as 'lifestyle migrants') who, since in 1980s, have decided to move to the same areas in the Marche Apennines in pursuit of a simpler, more 'authentic', way of life. The article shows that these dynamics, quite different at a first glance, have a common factor, which is the connection with the Marche landscape and the attributes attached to it.